Sparking The Impact Of Compensation, Work Motivation, Leadership On Employee Productivity - Saksono, Lalang; Ekasari, Silvia; Nurdiani, Tanti Widia; Tammubua, Milcha Handayani; Marihi, Laode (International Journal of Economics Development Research (IJEDR), 2024)
Research to test the effect of compensation, work motivation, leadership on employee work productivity at PT XYZ in Jakarta. This research uses a quantitative method with multiple linear regression analysis. Data were collected using questionnaires distributed to all employees of PT XYZ in Jakarta. The sampling technique used a census sampling technique with a population of 173 employees. The results of the research show that partially and simultaneously the variables of compensation, work motivation, leadership have a positive and significant effect on employee work productivity at PT XYZ in Jakarta. This finding can be a reference for PT XYZ in Jakarta to increase employee work productivity which has a good impact on organizational performance.